Causative factors of deep vein thrombosis of lower limb in Indian population - Khadilkar, Reina; Bhatnagar, Shubhi P.; Dave, Preet (International Surgery Journal, 2017)
Background: Deep vein thrombosis refers to the formation of an abnormal coagulum within the deep venous system. An accurate diagnosis of DVT is extremely important to prevent potentially fatal acute complications of pulmonary embolism (PE) and long-term complications of post phlebitis syndrome and pulmonary hypertension. There are many causative factors for DVT. Methods: This was a prospective study where 50 cases of DVT were admitted in this centre. Patients were evaluated in terms of causative factors of DVT. These were previous history of DVT, immobility, surgery, smoking, obesity and drugs. Age and gender comparisons were also done. The most common causes were recorded. Results: The most common cause was found to be immobility and post-surgery immobilization which constituted 90 % of the patients in the study. Advanced age and male gender showed a higher incidence of DVT. Conclusions: Early identification of the causes and the risk factors in the development of DVT can reduce the burden of the disease and contribute to its prevention and management.